Changes in the mechanical properties of the thigh and lower leg muscle-tendon units during the early follicular and early luteal phases - Saito, Rina; Shagawa, Mayuu; Sugimoto, Yuzuka; Hirai, Tomoki; Kato, Koyo; Sekine, Chie; Yokota, Hirotake; Hirabayashi, Ryo; Ishigaki, Tomonobu; Akuzawa, Hiroshi; Togashi, Ryoya; Yamada, Yuki; et al. (Frontiers in Sports and Active Living, 2024)
Background: This study aimed to determine changes in the muscle and tendon stiffness of the thigh and lower leg muscle-tendon units during the early follicular and early luteal phases, and check for possible relations between muscle and tendon stiffness in each phase.The sample consisted of 15 female university students with regular menstrual cycles. The basal body temperature method, ovulation kit, and salivary estradiol concentration measurement were used to estimate the early follicular and early luteal phases. A portable digital palpation device measured muscletendon stiffness in the early follicular and early luteal phases. The measurement sites were the rectus femoris (RF), vastus medialis (VM), patellar tendon (PT), medial head of gastrocnemius muscle, soleus muscle, and Achilles tendon.No statistically significant differences in the thigh and lower leg muscle-tendon unit stiffness were seen between the early follicular and early luteal phases. Significant positive correlations were found between the stiffness of the RF and PT (r = 0.608, p = 0.016) and between the VM and PT (r = 0.737, p = 0.002) during the early luteal phase.The present results suggest that the stiffness of leg muscle-tendon units of the anterior thigh and posterior lower leg do not change between the early follicular and early luteal phases and that tendons may be stiffer in those women who have stiffer anterior thigh muscles during the early luteal phase.